Application of SWAT Model in Assessing Impacts of FMNR on Water Conservation in Ndabibi Central Rift, Kenya - Kigen, Charles; Chesire, Michael; Korir, Janet; Munyao, Carol; Too, Prisca (International Journal of Environmental Sciences, 2025)
The Ndabibi watershed is predominantly agricultural that impacts its hydrological functions and water balance. This manifest through reduced watershed sponge effect, increased surface runoff during wet season and decreased surface runoff during the dry season, a situation that can be reversed by Farmer Managed Natural Regeneration (FMNR). FMNR is a conservation technique where trees/shrubs/ and other woody plants are allowed to grow naturally with minimal management by a farmer. Its application increases vegetation cover thereby reducing surface runoff. This study sought to establish the impact of FMNR on water conservation. The impact of this technique on surface runoff was quantified using SWAT (Soil and Water Assessment Tools) model. The watershed is ungauged and relied on regionalization with an assumed adoption of 20% FMNR in the watershed. The SWAT model under FMNR was calibrated with coefficient of variation (R2) of 0.95 for 20% and Nash-Sutcliffe of 0.88 on monthly time scale. The monthly streamflow analysis showed that there is a significant change in surface runoff ranging from -21.2% to 24.07% during the wet and dry seasons respectively. The study concludes that there is significant benefit of FMNR in regulating water balance in a given watershed and recommends its widespread adoption.